Coverage by examinations associated with early detection of colorectal neoplasia in the Czech Republic - Ngo, Ondřej; Hejcmanová, Kateřina; Suchánek, Štěpán; Pehalová, Lucie; Dušek, Ladislav; Zavoral, Miroslav; Bureš, Jan; Seifert, Bohumil; Hejduk, Karel; Král, Norbert; Májek, Ondřej (European journal of public health, 2023)
BACKGROUND: Coverage by examinations is a crucial indicator of the future impact on the burden of colorectal cancer (CRC). The study aimed to evaluate coverage by examinations associated with CRC screening and early cancer detection of CRC in the Czech Republic. The burden of CRC was also assessed. METHODS: The novel nationwide administrative registry with individual data (period 2010-19) was used to evaluate coverage by examinations for screening faecal occult blood test and colonoscopy. In the second step, additional examinations for early CRC detection were included in the coverage calculation (complete coverage). Age-specific trends in CRC incidence (period 1977-2018) were investigated using Joinpoint regression. RESULTS: Coverage by screening examinations within recommended interval was around 30%. Complete coverage reached >37% and >50% at the 3-year interval. The coverage by examinations for the non-screening population aged 40-49 years was almost 4% and 5% (most of them were colonoscopies) at the 3-year interval. In age groups aged ≥50 years, we observed a significant annual decline, especially in the 50-69 age group, with recent annual decreases reaching up to 5-7%. The change in trend and the recent decline were also observed in the age group 40-49. CONCLUSIONS: More than half of the target screening population was covered by examinations potentially associated with early detection and subsequent treatment of colorectal neoplasms. The substantial coverage by potentially prophylactic examinations might be an explanation for the considerable decrease in CRC incidence.
Keywords: Mass Screening; okultní krev; Registries; časná detekce nádoru; Aged; plošný screening; Humans; Early Detection of Cancer; Česká republika; kolorektální nádory; senioři; lidé; Middle Aged; lidé středního věku; Occult Blood; Colorectal Neoplasms; registrace; Czech Republic